Modelado y simulación del sistema de destilación de la planta piloto de alcohol de la UNAP-fiq, para la obtención de bioetanol carburante - García Pérez, Víctor (2017)
The present degree thesis consists of simulating the process of obtaining bioethanol fuel from the azeotrope mixture of ethanol and water; Using the steady-state heterogeneous azeotropic distillation method and n-pentane as the separating agent. The first phase consisted in the review of vapor liquid equilibrium, the thermodynamic model used, is the NRTL model, which describes the behavior of organic mixtures with presence of water, based on the concept of local composition, applicable to partially miscible systems, The virtual flow diagram of the process was elaborated, the different equipments were described, and the simulation of the process was carried out, using the simulator Chemcad v 6.1. The simulation according to the implemented flow diagram presents a bioethanol product with a concentration of 99.99 mol%, a mixture of ethanol and water fed to 84 mol% of ethanol, this product obtained is of high purity, superior to the azeotrope point, concluding that can be used in internal combustion engines.